Hubungan Indeks Massa Tubuh dan Tingkat Aktivitas Fisik dengan Kontrol Glikemik Diabetes Melitus Tipe 2 - Marisa Gita Putri; Heri Nugroho; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: Diabetes mellitus (DM) type 2 is still a serious health problem in the world. Type 2 DM results from ineffective use of insulin by the body. Most people with type 2 diabetes worldwide are the result of being overweight and lacking physical activity. The purpose of this study was to determine the relationship of body mass index and physical activity with the glycemic control of type 2 DM patients.Methods: This study used an observational study with a cross sectional design conducted at the Panti Wilasa Citarum Hospital in Semarang. The population in this study were outpatients at Panti Wilasa Citarum Hospital with a sample of 74 people. The sampling technique was consecutive sampling. Measurement of glycemic levels with HbA1c, body mass index based on weight and height, and physical activity with the PAR-WHO questionnaire. Data analysis uses the Spearman Rank correlation test. Result: From 74 research respondents found 52.7% of respondents had bad glycemic control. There is a relationship between body mass index and poor glycemic control (p = 0.041). There is no relationship between physical activity and poor glycemic control (p = 0.437).Conclusion: The advice given for respondents is to be able to maintain their diet and increase physical activity by exercising regularly.